2000
DOI: 10.1021/ac991087d
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction Coupled On-Line to a Reversed Micellar Mediated Chemiluminescence Detection System for Trace-Level Determination of Atropine

Abstract: A fast and sensitive method for the determination of atropine, an alkaloid closely related to cocaine, is proposed. The principles of on-line ion-pair formation of alkaloid-metal complexes and liquid-liquid extraction are applied to the chemiluminescence determination of atropine. On mixing with a reversed micellar medium of cetyltrimethylammonium chloride in dichloromethane-cyclohexane (1:1 v/v)-water (0.3 M Na2CO3) containing luminol, the ion-pair complex of tetrachloroaurate(III) with atropinium produced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…The CL signal increased with an increase in the Rw value. It has been observed that such a relationship between the CL intensity and Rw usually existed for the RMM-CL reaction of luminol, 3,4,6,8,[18][19][20]33,35,36 which may be facilitated by the generation of bulk-like water in the reversed micellar water pool at higher Rw. With the RB-Ce(IV) CL reaction, a similar effect of reversed micellar microenvironment seems to be the case.…”
Section: Effect Of the [H2o]/[ctac] Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The CL signal increased with an increase in the Rw value. It has been observed that such a relationship between the CL intensity and Rw usually existed for the RMM-CL reaction of luminol, 3,4,6,8,[18][19][20]33,35,36 which may be facilitated by the generation of bulk-like water in the reversed micellar water pool at higher Rw. With the RB-Ce(IV) CL reaction, a similar effect of reversed micellar microenvironment seems to be the case.…”
Section: Effect Of the [H2o]/[ctac] Ratiomentioning
confidence: 99%
“…3 In order to achieve enhanced sensitivity and improved selectivity in addition to other advantages, the CTAC reversed micellar medium has been successfully used to combine a solvent-extraction technique with the CL detection system based on the luminol oxidation in our previous studies. [15][16][17][18][19][20] After solvent extraction, it is possible to mix the extract directly with a reversed micellar solution of luminol dispersed in oil. Thus, we can avoid a relatively tedious procedure, like back extraction into the aqueous phase or evaporation of the solvent, which is required to use conventional aqueous solutions for CL measurements.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Using cetyltrimethylammonium chloride (CTAC) reverse micelles as micro-reactors in CL analysis, we have developed a flow-injection method based on a reversed micellar-mediated CL detection following solvent extraction. [6][7][8][9] In our previous studies concerning a luminol CL reaction with metal complexes in the CTAC reversed micellar solution, 10,11 it has been noted that the dissociation of metal complexes occurs at the reversed micellar interface, and that the released metal ions subsequently catalyze the CL reaction in the reversed micellar aqueous phase immediately after metal uptake by the reverse micelle into the water pool. In the uptake process, the reversed micellar interface has been regarded as being significant.…”
Section: Introductionmentioning
confidence: 99%
“…Until 1987, almost all of the micelleenhanced analytical procedures reported had utilized normal aqueous micelle systems. Consideration of so-called reversed micelles in CL measurements or [60], iron(III) [54,61], iron(II) [61], vanadium(IV) [55,62], atropine [63] and iodide and/or iodine [64].…”
Section: Reversed Micellesmentioning
confidence: 99%